An Experimental Study on the Shear Behavior of T-Beams Strengthened with Fiber Reinforced Polymers - Prasetiawan, Jauhari; Antonius; Setiyawan, Prabowo; Makrifa, Auliya Isti (Engineering, Technology & Applied Science Research, 2026)
This study presents an experimental and analytical investigation of shear strengthening for Reinforced Concrete (RC) T-beams using externally bonded carbon-fiber-reinforced polymer in U-wrap and side-bonded configurations and externally anchored steel strips. Fourteen identical T-beams were tested under four-point bending to create a shear-critical region near the support. The variables were the strengthening system, the number of carbon-fiber layers (one to three), and the presence or absence of internal stirrups (6 mm diameter at 200 mm spacing). Concrete compressive strength was 25 MPa. The carbon-fiber material had an ultimate tensile strength of 4900 MPa, an elastic modulus of 240 GPa, and a nominal thickness of 0.167 mm per layer. Load and deflection were recorded with a load cell and displacement transducers to evaluate stiffness and ductility, while crack development and failure modes were documented. All strengthened beams increased the maximum load relative to the reference beam with stirrups. U-wrap strengthening with stirrups provided the highest gain (40%–44%). Side-bonded strengthening showed lower gains due to premature end-debonding. Anchored steel strips achieved comparable enhancement (up to 43%) and promoted a shear–flexure response. ΡΨ Cross Section Analysis predictions were compared with experimental shear capacities to identify conservatism or overestimation and support calibration for design.